Prevention of Mental Health Difficulties for Children Aged 0–3 Years: A Review - Izett, Elizabeth; Rooney, Rosanna; Prescott, Susan L.; De Palma, Mia; McDevitt, Maryanne (Frontiers in Psychology, 2021)
Early life is a critical time for interventions to prevent future mental health problems. The first signs of mental health difficulties can be manifest in infancy, emphasising the importance of understanding and identifying both protective and risk factors in pregnancy and the early postnatal period. This will inform prevention efforts targeting both parents and their infants, such as infant attachment and early life events. Parents are also at a higher risk of developing mental health problems during the perinatal period, and an understanding of the predisposing factors is vital to this process. Here we review the existing prevention or treatment interventions in the early years—the majority targeting the parents in order to improve mental health for both children (focusing on the period from birth to three years) and parents. Elements of successful programs for parents include psychoeducation and practical skills training, as well as work on the co-parenting relationship, developing secure attachment, and parental reflective functioning. Cognitive-behavioural and interpersonal approaches also show promise. Targeted programs appear to display larger effects than universal programs. In synthesising this information, our goal is to inform the development of integrated models for prevention and novel early intervention programs as early as possible.